Identification, purification, and some physicochemical properties of staphylococcal enterotoxin C3. - Reiser, R F (1984)
A third staphylococcal enterotoxin C (C3) has been identified, purified, and characterized. Staphylococcal enterotoxin C3 was identified from a Staphylococcus aureus isolated received from England. The purified toxin was determined by gel permeation chromatography and sodium dodecyl sulfate-polyacrylamide gel electrophoresis to be a simple protein with a molecular weight of 26,900. The isoelectric point of the major band was determined by isoelectric focusing in polyacrylamide gels to be 8.15. The reaction of enterotoxin C3 with its specific antibody was not affected by tryptic digestion at pH 8.0 or peptic digestion at pH 4.5. The enterotoxin C3 consisted of 236 amino acid residues. Serine was shown to be the NH2-terminal amino acid residue by end group analysis. The protein was highly emetic in cynomolgus monkeys both per os and intravenously.